2011
DOI: 10.1111/j.1524-4741.2011.01204.x
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Breast MRI in the Surgical Treatment of Ductal Carcinoma In Situ

Abstract: Accurate determination of the size or extent of ductal carcinoma in situ (DCIS) by imaging is uncertain, and incomplete resection of tumor results in involved margins in up to 81% of cases. This study examined the accuracy of magnetic resonance imaging (MRI) for assessment of DCIS size, and evaluated the effect of preoperative breast MRI on achievement of tumor-free surgical margins after breast-conserving surgery (BCS). One-hundred and fifty-eight female patients with DCIS were identified from a prospective d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 37 publications
2
23
0
Order By: Relevance
“…Nine studies were eligible for the meta‐analysis; seven of these were studies that compared cohorts defined by whether or not MRI was performed, and two were RCTs of preoperative MRI. Four studies included patients with both DCIS and invasive breast cancer, whereas five included patients with DCIS only. Four studies included patients undergoing BCS as primary surgery, whereas five evaluated preoperative MRI in patients scheduled for either mastectomy or breast conservation as initial surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies were eligible for the meta‐analysis; seven of these were studies that compared cohorts defined by whether or not MRI was performed, and two were RCTs of preoperative MRI. Four studies included patients with both DCIS and invasive breast cancer, whereas five included patients with DCIS only. Four studies included patients undergoing BCS as primary surgery, whereas five evaluated preoperative MRI in patients scheduled for either mastectomy or breast conservation as initial surgery.…”
Section: Resultsmentioning
confidence: 99%
“…The extent of disease within the breast and the presence of multifocality, which in turn affect the ability to achieve negative margins, heavily influence surgical planning (Dick et al 2011) but, unfortunately, precise preoperative assessment of DCIS extension remains elusive because traditional clinical evaluation proved unreliable (Holland et al 1985) and recent diagnostic tools showed some limitations as well. MRI can in facts detect DCIS (in particular high- or intermediate-grade lesions) but it does not accurately predict the size of the tumor and does not improve the surgeon's ability to achieve clear margins following breast-conservative surgery (Kropcho et al 2012). …”
Section: Discussionmentioning
confidence: 99%
“…17 A more recently published prospective study of 158 women with DCIS found a significantly higher mastectomy rate associated with preoperative MRI and no improvement in reexcision rates (Table 2). 18 …”
Section: Discussionmentioning
confidence: 99%